POLA ASUH ORANG TUA DALAM PENGEMBANGAN KARAKTER ANAK TUNAGRAHITA RINGAN DI SLB PKK GEDEG MOJOKERTO - SEPTA PRIYANTINI, BELLA; MAHMUDAH, SITI (Jurnal Pendidikan Khusus, 2018)
This research approach used is qualitative approach with descriptive study type. Data collection techniques are done by interview, and documentation. Research subjects were 5 parents and 5 children with intellectual disorder. Data analysis technique is by using data stages, data reduction, data presentation, and conclusion reduction. The results of this study indicate that as many as 3 parents (60%) use permissive parenting as the dominant parenting pattern and as many as 2 parents (40%) use authoritative parenting as the dominant parenting pattern. How to develop the character of a child with mild intellectual disorder in each parent is different including the character values ??applied to the five children with mild intellectual disorder are also different. Constraints in the face and the solution provided by each parent is also different to adjust the state of child with intellectual disorder. Parenting gives a big role in developing character in children with mild intellectual disorder. In permissive parenting parents role to give freedom to children choose the value of characters that child is doing. While in the parenting authoritative parents role plays a target in the childs intellectual disorder in developing character.Keywords: parenting pattern, character development, child with mild intellectual disorder.